A simple structural control model for earthquake excited structures. (1st March 2019) - Yanik, Arcan; Aldemir, Unal
Highlights: An integrated active and semi-active control system is presented in this paper. A simple control approach is proposed. A building with an active tendon controller system and an MR damper is considered. Time-delays and electrical current need of the MR damper are taken into account. Abstract: The biggest challenge and criticism on active control systems in earthquake engineering applications point out the issues that could occur because of a possible power loss of the active controller system during an earthquake. The power supply of an active control system can be disabled during an earthquake. This study is written to introduce a simple structural model to overcome the challenges defined above, and to investigate the performance of this system. The integrated active and semi-active control system is named as "INASA." The proposed control method of the INASA system both minimizes integrated active and semi-active control energy, as well as the structural energies. A building with an active tendon controller system, with the integration of an MR damper, is considered as an example structure. For numerical validation of the INASA system, near-fault and far-fault earthquakes are used. The electrical current need for operation of the MR damper as well as the time-delay effects of the active tendon controllers are also taken into account for more realistic dynamic simulations. The dynamic performance of the INASA system under different earthquakes is compared to the building equipped with the MR damper the conventional uncontrolled structure. The results showed that the INASA system could work without any stability problems under both earthquakes. Time-delays did not have a negative effect on the system. And a reasonable reduction in uncontrolled response is achieved with very small power requirement. In the possible case of a power loss, the deactivation of the active tendon control system did not lead to a discrepancy, because the MR damper continued to operate with a very small power requirement and showed a good performance.